ROBOT OPERATING SYSTEM (ROS) DAN GAZEBO SEBAGAI MEDIA PEMBELAJARAN ROBOT INTERAKTIF - Jalil, Abdul (Program Studi Teknik Informatika Fakultas Ilmu Komputer Univeristas Muslim Indonesia, 2018)
A robot is a prototype that is able to control by automatically to help the human work. Some of the parts to build a robot system are making the mechanical system, hardware, and software. The limitation of cost to make the robot hardware and programming skills are an obstacle to learn and develop the robot system. The development of the robot community nowadays makes the Robot Operating System (ROS) and Gazebo as an interactive media to learn and make the robot simulation. ROS is a middleware that equipped with tools and libraries to create a robot software, while Gazebo is a 3D simulation application to build a robot hardware design. On this paper, the researcher makes a robot simulation to avoid the object using Lidar sensor and camera, the simulation has developed using ROS and Gazebo that be able to use as a media for robot learning interactive.